2005
DOI: 10.1007/s11242-004-6143-3
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Blowing and Suction on Double Diffusion by Mixed Convection over Inclined Permeable Surfaces

Abstract: A boundary layer analysis is used to investigate the effect of lateral mass flux on mixed convection heat and mass transfer over inclined permeable surfaces in porous media. The conservation equations that govern the problem are reduced to a system of non-linear ordinary differential equations and then the resulting equations is solved by numerical method. The numerical results for heat and mass transfer in terms of Nusselt and Sherwood number are presented in x-y plots for the buoyancy ratio (N ) and Lewis nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…This is logic since the only factor tuned at a constant Prandtl number is the Schmidt value of the fluid. Similar behaviors were found by several works such as Bansod (2005). He investigated blowing and suction effects on double diffusion by mixed convection over inclined permeable surfaces.…”
Section: Combined Effect Of Suction or Blowing Slot Length And Lewis supporting
confidence: 78%
See 1 more Smart Citation
“…This is logic since the only factor tuned at a constant Prandtl number is the Schmidt value of the fluid. Similar behaviors were found by several works such as Bansod (2005). He investigated blowing and suction effects on double diffusion by mixed convection over inclined permeable surfaces.…”
Section: Combined Effect Of Suction or Blowing Slot Length And Lewis supporting
confidence: 78%
“…The difference is attributed to the control position relative to the natural vortex emission point that is now upstream of the slot. Earlier study of Bansod (2005) showed that heat and mass transfer increase with suction and decrease with blowing. Herein we also found that , and ℎ are increased by suction compared to blowing.…”
Section: Starting Frommentioning
confidence: 97%
“…Thus, for the buoyancy assisting flow condition, Hooper et al [2] found that suction increases, whereas injection decreases, the rate of heat transfer at the wall. Bansod [3] stated the same result, but for the opposing flow the rates of heat and mass transfer decreases in a porous media whatever suction or injection, as explained above. Due to lower surface transfer, Chamkha [4] observed that the Nusselt for mixed convection in porous media fall as the parameter of injection increases.…”
Section: Introductionmentioning
confidence: 60%
“…Bansod [19] investigated the Darcy model for boundary layer flows in a horizontal porous medium induced by combined buoyancy forces. Bansod [20] studied the effects of blowing and suction on double-diffusion by mixed convection over inclined permeable surfaces. Postelnicu [21] studied the influence of chemical reaction on heat and mass transfer by natural convection from vertical surfaces in porous media considering Soret and Dufour effects.…”
Section: Introductionmentioning
confidence: 99%